THE ROLE OF EASTERN THEMES IN RUSSIAN SOVIET POETRY IN THE NEAR ABROAD WORLDVIEW OF STUDENTS IN RUSSIAN LANGUAGE LESSONS - Togamurodova Jasmina Zhamolovna; Yusupova Idrisakhon Bakhtiyorovna; Irbutaeva Nigora Dilshodovna (World Scientific Research Journal, 2025)
Abstract: This article discusses the perception of S. Yesenin's lyrics and the international education of students in Russian language classes through Yesenin's works. About his famous cycle "Eastern Motifs". About how a poet bows before the beauty of the world, strives for harmony of feelings, in search of happiness and goodness. About the aesthetic equality of two worlds.